1999
DOI: 10.1007/s004970050170
|View full text |Cite
|
Sign up to set email alerts
|

Apomixis and sexuality in diploid and tetraploid accessions of Brachiaria decumbens

Abstract: Meiotic and aposporous embryo sacs and the initial steps of parthenogenetic embryogenesis and endosperm formation were investigated in diploid and tetraploid accessions of Brachiaria decumbens in two environments, differing mainly in day length: early summer and late autumn. Both diploid and tetraploid accessions were facultative apomicts. Di(ha)ploids showed a much lower level of apomixis (10% to15%) than tetraploids (80% to 95%). No obligate sexual diploids were found; thus, their occurrence in natural popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 20 publications
4
48
0
1
Order By: Relevance
“…It has been suggested that, for many species, only diploid or polyploid gametes may carry the alleles for apomixis and that haploid gametes are selected against or have developmental abnormalities (Nogler 1984;Naumova et al 2001). In some cases, however, diploid apomicts have been recorded from the field (Jankun & Kovanda 1988;Naumova et al 1999Naumova et al , 2001) and haploid transfer of apomixis has been noted (Bicknell et al 2000), indicating that this effect may be associated with the genomic organisation of individual taxa, rather than a feature of apomixis per se. Given the close association of apomixis and polyploidy, it is perhaps most likely that in Coprosma the functional diploid chromosome number of 2n = 44 actually represents a tetraploid complement with a basic number of x = 11.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that, for many species, only diploid or polyploid gametes may carry the alleles for apomixis and that haploid gametes are selected against or have developmental abnormalities (Nogler 1984;Naumova et al 2001). In some cases, however, diploid apomicts have been recorded from the field (Jankun & Kovanda 1988;Naumova et al 1999Naumova et al , 2001) and haploid transfer of apomixis has been noted (Bicknell et al 2000), indicating that this effect may be associated with the genomic organisation of individual taxa, rather than a feature of apomixis per se. Given the close association of apomixis and polyploidy, it is perhaps most likely that in Coprosma the functional diploid chromosome number of 2n = 44 actually represents a tetraploid complement with a basic number of x = 11.…”
Section: Discussionmentioning
confidence: 99%
“…One of them is called the "diploid-tetraploid-diploid cycle." Paspalum is one such genus where a breeding population mostly consists of facultative apomictic tetraploids, sexual diploids, triploids, and aneuploids (see Naumova et al [1999] for a relatively recent reference). Thus, there are populations that could, in theory, help establish a polyploid "event."…”
Section: Details On the Origin Of Paleopolyploidsmentioning
confidence: 99%
“…Ovule and seed development For the study of ovule and seed development, whole ovaries and siliques were fixed in either FAA or Carnoy's solution and cleared as in Naumova et al (1999). The ovules and seeds from individual ovaries and siliques, respectively, were mounted on separate slides for further investigation.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Ploidy levels of leaf cells were determined using flow cytometry. Suspensions of intact leaf nuclei were prepared (Arumuganathan and Earle 1991;Naumova et al 1999) and analyzed using a Beckman-Coulter EPICS XL-MCL flow cytometer (Miami, Fla.) equipped with an argon ion laser at 488 nm. The ploidy of embryo and endosperm nuclei was determined in single mature seeds using a Partec Flow Cytometer PA (Münster, Germany) and the Flow Cytometric Seed Screen (FCSS; Matzk et al 2000Matzk et al , 2001.…”
Section: Ploidy and Pollen Analysismentioning
confidence: 99%